NUMERICAL STUDY ON THERMAL PERFORMANCE OF MINI-CHANNEL COOLING ON CYLINDRICAL LITHIUM-ION BATTERY COOLING SYSTEM - Elvi Ermadani; James Julian; Bima Rakha Adhitama; Fitri Wahyuni; Riki Hendra Purba; Fathin Muhammad Mahdhudhu; Adi Winarta (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
This study investigates how a liquid-based cooling configuration influences the thermal behavior of a cylindrical lithium-ion (Li-ion) battery pack through numerical analysis. The work underscores the crucial role of proper thermal regulation to maintain operational safety and prolong battery lifespan in high-demand applications such as electric vehicles (EVs). Three cooling-channel diameters—4, 6, and 8 mm—were examined under a 5C discharge condition. The findings indicate that the 8 mm channel offers the most advantageous performance, delivering the lowest maximum temperature, quicker thermal stabilization, and improved temperature uniformity. Conversely, the 4 mm channel resulted in elevated peak temperatures and a temperature gradient (ΔT) of 8.3 °C, which may intensify hotspot formation and accelerate cell degradation. Overall, the results emphasize the importance of selecting an appropriate cooling-channel diameter to effectively mitigate thermal stress.